COORDINATE CALCULATION OF VEHICLE WHEEL GEOMETRICAL CENTER - A. K. Grishchuk; A. V. Shcherbina (Наука и техника)
The paper describes a necessity to take into account toe-in angles while making calculations of suspension kinematics. An algorithm for determination of vehicle wheel center coordinates with due account of camber and toe-in angles is presented with the help of turn matrices.  The obtained formulas describing functional dependence of vehicle wheel centre coordinates on camber and toe-in angles allow to reduce a general error in calculations and mathematical models for  operation of running gear and steering mechanisms.